The study of questions. Issue 1 (15th June 2020) - Moyer, Morgan C.; Syrett, Kristen
Abstract: Asking questions is a fundamental aspect of human nature. Languages all around the world encode interrogative constructions. It is therefore incumbent upon semanticists to capture the meaning of questions. However, achieving this goal faces a challenge under a truth conditional approach to meaning, since questions cannot easily be assigned a truth value. Moreover, it is not sufficient to focus only on the questions themselves; one must also determine what counts as a felicitous and informative answer, and how this relates to a speaker's intention in posing a question in a discourse context. How then do semanticists approach an investigation of questions? In this article, we present the core issues inherent to question‐answer dynamics, review the main approaches to question‐answer meaning, highlight how questions are situated in a discourse context, and explore extensions of questions that highlight the connection between semantics, pragmatics, and human reasoning. This article is categorized under: Linguistics > Linguistic Theory